A Mouse Model of Creatine Transporter Deficiency Reveals Impaired Motor Function and Muscle Energy Metabolism - Stockebrand, Malte; Sasani, Ali; Das, Devashish; Hornig, Sönke; Hermans-Borgmeyer, Irm; Lake, Hannah A.; Isbrandt, Dirk; Lygate, Craig A.; Heerschap, Arend; Neu, Axel; Choe, Chi-Un (Frontiers in Physiology, 2018)
Creatine serves as fast energy buffer in organs of high-energy demand such as brain and skeletal muscle. L arginine:glycine amidinotransferase (AGAT) and guanidinoacetate N methyltransferase (GAMT) are responsible for endogenous creatine synthesis. Subsequent uptake into target organs like skeletal muscle, heart and brain is mediated by the creatine transporter (CT1, SLC6A8). Creatine deficiency syndromes (CDS) are caused by defects of endogenous creatine synthesis or transport and are mainly characterized by intellectual disability, behavioral abnormalities, poorly developed muscle mass, and in some cases also muscle weakness. CT1-deficiency is estimated to be among the most common causes of X-linked intellectual disability and therefore the brain phenotype was the main focus of recent research. Unfortunately, very limited data concerning muscle creatine levels and functions are available from patients with CT1 deficiency. Furthermore, different CT1-deficient mouse models yielded conflicting results and detailed analyses of their muscular phenotype are lacking. Here, we report the generation of a novel CT1-deficient mouse model and characterized the effects of creatine depletion in skeletal muscle. HPLC-analysis showed strongly reduced total creatine levels in skeletal muscle and heart. MR-spectroscopy revealed an almost complete absence of phosphocreatine in skeletal muscle. Increased AGAT expression in skeletal muscle was not sufficient to compensate for insufficient creatine transport. CT1-deficient mice displayed profound impairment of skeletal muscle function and morphology (i.e., reduced strength, reduced endurance, muscle atrophy). Furthermore, severely altered energy homeostasis was evident on magnetic resonance spectroscopy. Strongly reduced phosphocreatine resulted in decreased ATP/Pi levels despite an increased inorganic phosphate (Pi) to ATP flux. Concerning glucose metabolism, we show increased glucose transporter type 4 expression in muscle and improved glucose clearance in CT1-deficient mice. These metabolic changes were associated with activation of AMP-activated protein kinase (AMPK) – a central regulator of energy homeostasis. In summary, creatine transporter deficiency resulted in a severe muscle weakness and atrophy despite different compensatory mechanisms.